1975
DOI: 10.1002/cjce.5450530504
|View full text |Cite
|
Sign up to set email alerts
|

Experimental testing of the hydrodynamic collision model of fine particle flotation

Abstract: Flotation rates of glass beads and of latex particles have been measured as a function of particle size using very small bubbles. With glass beads the observed rate versus size relationship agreed quite well with the prediction of a simple hydrodynamic collision model, but that found with latex particles did not. It is suggested that electrical forces may have to be taken into account when the particles have a significant zeta potential. With both types of particle, the relationship between flotation rates mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(37 citation statements)
references
References 4 publications
3
31
0
Order By: Relevance
“…The increase in coal floatability in electrolyte solutions may be attributed to compression of the electrical double layer and the resulting reduction of the zeta potentials, which minimize the long-range repulsive forces between the bubble and the particle. This mechanism is supported by the experimental data showing that flotation recovery reaches a maximum at minimum zeta potentials (4,6,7). However, the recovery of the coal flotation in electrolyte solution often does not reach maximum at the solution pH where the zeta potential is zero.…”
Section: Introductionmentioning
confidence: 50%
“…The increase in coal floatability in electrolyte solutions may be attributed to compression of the electrical double layer and the resulting reduction of the zeta potentials, which minimize the long-range repulsive forces between the bubble and the particle. This mechanism is supported by the experimental data showing that flotation recovery reaches a maximum at minimum zeta potentials (4,6,7). However, the recovery of the coal flotation in electrolyte solution often does not reach maximum at the solution pH where the zeta potential is zero.…”
Section: Introductionmentioning
confidence: 50%
“…The collision efficiencies are then determined by using a first order kinetic model (19) to model the particle removal rates. Reay and Ratcliff (17,38) have shown that flotation collision efficiencies should increase with increasing particle size as E c ϳ a 2 N , where the value of N ranges from 0.5-2 depending on the properties of the solid being floated and the type of surfactants being used. Experiments by Ahmed and Jameson (39) and those of Reay and Ratcliff (17) suggest that the collision efficiency increases with decreasing bubble size as E c ϳ a 1 Ϫ2 .…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
“…Particles less than 0.6 µm were also discarded because they were below the detection limit of our particle counter (Coulter Multisizer II, with 50 µm orifice). The experimentally constrained choice of working with colloids in the 0.6 to 1.0 µm range is disadvantageous from considerations of particle-bubble collision efficiency since finer sizes permit more Brownian encounters while larger sizes permit inertial contact (24,25).…”
Section: Preparation Of Colloid Suspensionsmentioning
confidence: 99%